Discriminating Between Autocorrelation and Misspecification in Regression Analysis: An Alternative Test Strategy - Godfrey, Leslie G. (The Review of Economics and Statistics, 1987)
Leslie G. Godfrey, Discriminating Between Autocorrelation and Misspecification in Regression Analysis: An Alternative Test Strategy, The Review of Economics and Statistics, Vol. 69, No. 1 (Feb., 1987), pp. 128-134